Coronavirus disease 2019 in proportion to population: a historical analysis of Saudi Arabia - Salam, Asharaf Abdul (2023)
There are a total of 750,998 infected cases, as of April 1, 2022 (2100 per 100,000 persons), with higher infection rates, but almost all recovered (734,820; 2055 per 100,000 persons), while the rest either passed away (9047; 25 per 100,000 persons) or were under treatment (7131; 20 per 100,000 persons). Thus, there is a narrow gap between infected and recovered persons, especially in the first two waves but different in the third wave. However, they are bridged at a faster pace, as shown in Fig. 1. It is the mortality from COVID-19 which has received greater concern in the country due to its ups and downs.